A Systematic Study of UML based Metrics and their uses - Sunil Sikka1, Priyanka Makkar, Anshu Malhotra (International Journal of Advanced Science and Technology, 2020)
At every stage of software development quality assurance should be carried out. The aim of this paper is to determine the different features covered by various UML diagrams. It is observed by the software practitioners that more time is taken to discover the defect in a system it will be more expensive to fix. By using metrics researcher can improve the quality of the software.